Pulmonary Pleomorphic Carcinoma Detected as a Result of Pneumothorax and the Subsequent Occurrence of Multiple Cystic Metastases. (20th August 2014) - Yamakawa, Hideaki; Yoshida, Masahiro; Yabe, Masami; Baba, Yuri; Baba, Emiri; Katagi, Hiroaki; Ishikawa, Takeo; Takagi, Masamichi; Nakada, Takeo; Akiba, Tadashi; Kuwano, Kazuyoshi
Abstract : A 39-year-old man was admitted for spontaneous pneumothorax. He underwent pulmonary resection to correct the lesion causing the air leakage, and a pathological diagnosis of pulmonary pleomorphic carcinoma was made because we thought that the pneumothorax developed due to the direct rupture of necrotic neoplastic tissue into the pleural cavity. After the operation, the patient received chemotherapy, during which multiple cystic metastases gradually developed in the lung that caused repeated occurrences of pneumothorax. Clinicians must be careful to recognize that pneumothorax can also be a complication of primary and various metastatic pulmonary malignancies.